RECEPTIVE LANGUAGE OF AUTISM-DEAF STUDENT - Hilma Rahmatillah; Hartini Nara; Trisna Mulyeni (Perspektif Ilmu Pendidikan, 2021)
This study aims to determine the receptive language shown by autism-deaf students. The subject in this study was an autism-deaf student at SLB Kembar Karya Pembangunan II. The research method used in this research is a case study with a qualitative research approach. The data was collected by observing, interviewing and documenting further data analysis in the field using the Miles and Huberman model. The results showed that the autistic-deaf students showed several receptive languages ​​that they had. The results shown are being able to match pictures, knowing nouns, being able to group colors and being able to follow instructions. These results indicate that autism-deaf students have receptive language and can develop language skills such as receptive and expressive language. Therefore, parents and teachers need to know the needs and abilities of autism-deaf students so that they can design appropriate activities and provide appropriate teaching and activities so that autistic-deaf students can develop receptive language skills.